A Novel Model on DST-Induced Transplantation Tolerance by the Transfer of Self-Specific Donor tTregs to a Haplotype-Matched Organ Recipient - Mohr Gregoriussen, Angelica Maria; Bohr, Henrik Georg (Frontiers in Immunology, 2017)
Abstract Donor specific blood transfusion (DST) can lead to significant prolongation of allograft survival in experimental animal models and sometimes human recipients of solid organs. The mechanisms responsible for the beneficial effect on graft survival have been a topic of research and debate for decades and are not yet fully elucidated. Once we discover how the details of the mechanisms involved are linked, we could be within reach of a procedure making it possible to establish donor specific tolerance with minimal or no immunosuppressive medication. Today, it is well established that CD4+ Foxp3+ regulatory T cells (Tregs) are indispensable for maintaining immunological self-tolerance. A large number of animal studies has also shown that Tregs are essential for establishing and maintaining transplantation tolerance. In this paper we present a hypothesis of one H2-haplotype matched DST induced transplantation tolerance (in mice). The formulated hypothesis is based on a re-interpretation of data from an immunogenetic experiment published by Niimi and colleagues in 2000. It is of importance that the naïve recipient mice in this study were never immunosuppressed and were therefore fully immune competent during the course of tolerance induction. Based on the immunological status of the recipients, we suggest that one H2-haplotype matched self-specific Tregs derived from the transfusion blood can be activated and multiply in the host by binding to antigen-presenting cells (APCs) presenting allopeptides in their MHC (major histocompatibility complex) class II (MHC-II). We also suggest that the endothelial and epithelial cells within the solid organ allograft up-regulate the expression of MHC-II and attract the expanded T-reg population to suppress inflammation within the graft. We further suggest that that this biological process, here termed MHC-II recruitment, is a vital survival mechanism for organs (or the organism in general) when attacked by an immune system.